2017
DOI: 10.1002/chem.201701286
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of Salicylate Dioxygenase: QM/MM Simulations Reveal the Origin of Unexpected Regioselectivity of the Ring Cleavage

Abstract: Salicylate 1,2-dioxygenase (SDO) was the first enzyme discovered, in the family of iron dioxygenases, to catalyze the ring cleavage of a monohydroxylated aromatic compound, salicylate, without a proton donor. Salicylate is not electron-rich like the familiar dihydroxy or aromatic substrates with an electron-donating group that are utilized in the well-known dioxygenases. SDO carries out the intramolecular C-C bond cleavage in salicylate bearing the OH and COOH groups with high regioselectivity in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 79 publications
6
24
0
Order By: Relevance
“…The dioxygen group has a superoxide character, and the opposite spin between the substrate radical and the superoxide (DHBP •↑ –Fe II –O 2 •–↓ ) can be the reactive state for the subsequent catalytic reaction. The above results are similar to many previous theoretical studies of the nonheme iron-containing extradiol dioxygenases. ,,,, To better understand the further insight into the quintet reactive state, molecular orbital diagram was obtained (Figure ), which indicates that the iron 3d orbitals could interact with the surrounding ligands and split into a pair of two π* orbitals (π xz * , π yz * ) and a pair of two σ* orbitals ( ). As shown in Figure , the π yz * and π xz * of the 3d orbitals in Fe II represent the antibonding combinations with the 2p orbital of dioxygen and DHBP, whereas the d xy orbital is not changed as there is not any antibonding interaction between iron and DHBP.…”
Section: Resultssupporting
confidence: 86%
“…The dioxygen group has a superoxide character, and the opposite spin between the substrate radical and the superoxide (DHBP •↑ –Fe II –O 2 •–↓ ) can be the reactive state for the subsequent catalytic reaction. The above results are similar to many previous theoretical studies of the nonheme iron-containing extradiol dioxygenases. ,,,, To better understand the further insight into the quintet reactive state, molecular orbital diagram was obtained (Figure ), which indicates that the iron 3d orbitals could interact with the surrounding ligands and split into a pair of two π* orbitals (π xz * , π yz * ) and a pair of two σ* orbitals ( ). As shown in Figure , the π yz * and π xz * of the 3d orbitals in Fe II represent the antibonding combinations with the 2p orbital of dioxygen and DHBP, whereas the d xy orbital is not changed as there is not any antibonding interaction between iron and DHBP.…”
Section: Resultssupporting
confidence: 86%
“…Our calculations indicated that this reaction is the rate-limiting step in the catalytic process. 3 studies on the non-heme iron-containing enzymes SDO and HPCD also obtained relatively high-energy barriers in the similar superoxo addition step (19.8 kcal/mol in SDO and 17.4 kcal/mol in HPCD), 28,31,38 which should be ascribed to that the substrates of these two enzymes, as well as the substrate 1 of SznF, are all featured with a conjugation π system in them.…”
Section: ■ Methods and Modelsmentioning
confidence: 83%
“…It is very common among the non-heme iron-containing enzymes such as SDO, 2,3dihydroxybiphenyl dioxygenase (BphC), and homoprotocatechuate 2,3-dioxygenase (HPCD) that simultaneously binding of the substrate and the dioxygen to the iron center generates Fe II −superoxo species and cationic substrate radical. 22,23,[25][26][27][28]38 It should be ascribed to that the electron-rich substrates of these enzymes are bound up with the iron center so that they can donate electrons to reduce the dioxygen through the iron center. As shown in Figure 2a, in 3 IntA HA , the Fe−O bond length is 2.01 Å.…”
Section: ■ Methods and Modelsmentioning
confidence: 99%
“…It has been extensively showed by theoretical studies that in many mononuclear non-heme enzymes the quintet FeÀ O 2 is the reactive species. [15,29,30,33,35,[38][39][40][41][42][43][44][45][46][47][48] As such, we took 5 1 side-on as the catalytically relevant state for the oxidative cleavage of resveratrol. The subsequent QM/MM calculations were carried out on the quintet surface.…”
Section: Reaction Mechanismmentioning
confidence: 99%